Leksikon Penamaan Gerabah Tradisional di Desa Sumedangan, Madura: Kajian Etnolinguistik - Akbar Yudho Wibowo; Ainur Rofiq Hafsi; Ria Kasanova (Lembaga Pengembangan Kinerja Dosen, 2026)
Social change and modernization may reduce the use of material cultural lexicons that function as media for transmitting local knowledge. One form of material culture that still preserves a traditional naming system is Madurese pottery. However, studies linking pottery nomenclature with linguistic representation and local wisdom among artisan communities remain limited. This study aims to identify and classify lexical units in the naming of pottery types and parts, as well as analyze the local wisdom values contained in them. This research applied a qualitative method with an ethnolinguistic approach. Data were collected through semi-structured interviews and documentation involving traditional pottery artisans in Sumedangan Village, Pademawu District, Pamekasan Regency, Madura. Data analysis included lexicon inventory, classification of naming principles, and ethnolinguistic interpretation of cultural values. The findings revealed 12 lexical units formed through five naming principles: distinctive properties, similarity, parts, sound imitation, and word shortening. The dominance of distinctive properties and similarity indicates that artisans construct cultural knowledge through practical object functions, bodily experience, and interaction with the environment. The naming system also reflects functional, ecological, and socio-spiritual values, confirming that language represents cultural knowledge and community identity. These findings support efforts to preserve Madurese cultural heritage through ethnolinguistic documentation sustainably.